BIOACTIVE AND FUNCTIONAL PROPERTIES OF FISH PROTEIN HYDROLYSATE FROM LEIOGNATHUS BINDUS - JOHNROSE PRABHA,; Vincent, Savariar; Joseph, Swapna; Magdalene, Joacy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present work is focused on the production of biologically active protein hydrolysate from low value by-catch fish, Leiognathus bindus; this will be an ideal approach to exploit the underutilized fish to develop a highly nutritious bioactive product. Moreover, fish protein hydrolysates have a broad spectrum of applications ranging from high-value peptones to food ingredients with special functional properties. Methods: The protein hydrolysate was prepared from L. bindus through acidic autolysis processes. The proximate composition, physico-functional, and biochemical properties of hydrolysate and control samples were characterized by standard protocols. Molecular profiling was done by sodium dodecyl sulfate polyacrylamide gel electrophoresis and high-performance liquid chromatography analysis performed to identify the essential amino acid composition in protein hydrolysate. Results: The results of this study reveals that the protein hydrolysate obtained from the trash fish has relatively high protein (71.01Â±0.2%) and low lipid (1.57Â±0.1%) content. The molecular analysis shows low molecular weight peptides are obtained in the hydrolyzed samples which indicate high protein solubility confirmed to have the potential application as an ingredient in the balanced human diet. The chemical score of the hydrolysate indicates that it fulfills adult human nutritional requirements. Conclusion: This approach also offers the relatively simple and cost-effective process to improve the nutritional characteristics and functional properties of foodstuff, also an opportunity for the conversion of waste fish resources to nutritious products, that can be used in food and pharmaceutical industries. Keywords: Protein hydrolysate, Emulsifying property, Bioactive, Peptides, Amino acid, Chemical score.